Impact of anti-VEGF therapy on choroidal thickness in patients with retinal vein occlusion: a systematic review and meta-analysis - Cheng, Xiner; Zeng, Xinwei; Liu, Shimei; Liu, Chang; Liu, Yulong; Xu, Guoxu (Frontiers in Medicine, 2025)
ObjectivesTo systematically review and analyze existing literature reporting changes in choroidal thickness at 1, 3, 6, and 12 months following anti-VEGF treatment in patients with retinal vein occlusion (RVO).MethodsA comprehensive literature search identified 16 eligible studies including a total of 545 patients and 547 eyes. Data were extracted on subfoveal choroidal thickness at baseline and at specified follow-up intervals. Meta-analyses were performed to assess pooled changes in choroidal thickness after treatment, and subgroup analyses were conducted based on anti-VEGF drug type and treatment regimen.ResultsAt 1- and 3-month follow-up, anti-VEGF therapy was associated with a significant reduction in choroidal thickness. By 12 months, choroidal thickness tended to return toward baseline levels, suggesting potential stabilization or structural adaptation. Subgroup analyses indicated that the effects on choroidal thickness may vary among different anti-VEGF agents, with ranibizumab and aflibercept showing significant early reductions, while bevacizumab demonstrated more delayed effects. Further subgroup analyses based on RVO type showed that at 1 month, choroidal thickness was significantly reduced in branch retinal vein occlusion patients, but not in central retinal vein occlusion patients, suggesting potential differences in drug response between RVO subtypes. However, given the limited number of studies within some subgroups, these findings should be interpreted with caution.ConclusionIn patients with RVO, anti-VEGF therapy appears to induce an early reduction in choroidal thickness, which tends to return toward baseline with longer follow-up. Subgroup analyses provided preliminary insights into the potential influence of different agents, disease subtypes, and treatment regimens. However, this study was limited by the small number of eligible studies and the heterogeneity of study designs. Therefore, the findings should be regarded as exploratory and interpreted with caution. Future prospective studies with larger sample sizes, standardized imaging protocols, and longer follow-up are needed to clarify the clinical relevance of choroidal thickness changes in RVO patients undergoing anti-VEGF therapy.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD 420251011228.